Effect of Job Security and Job Embeddedness on Turnover Intention: A Study of Pakistan's Textile Industry - Moazam Shahwar; Muhammad Amin; Maida Azhar; Mariam Pervaiz; Javeed Iqbal (Governance and Society Review, 2024)
This research aims at exploring how the influence of job security (JS) and job embeddedness (JE) affects turnover intention (TI). It also looks at how work engagement, (WENG) mediates the link between JS and JE in the sample of this study. A total of 380 workers from the textile industry of Pakistan were selected as the population. A correlation technique is used in survey research to analyze the link between distinct variables. The results showed that the key research variables are significantly related to one another. It turned out that the work engagement was essential in bridging the gap between JS, JE, and TI. The findings revealed that organizations especially human resource departments may use job embeddedness and job security as tools towards increasing work engagement and retention. The work expands the knowledge base in connection to important study considerations. The relationship between job security, job embeddedness, and employees' turnover intention is mediated by work engagement, which is the focus of this paper's mediating role analysis. The current research collected, compiled, and assessed individual researches that investigated the relationship. Therefore, it provides an overview of all the individual studies reviewed in the research where credible evidence has been provided to support the findings of the meta-analysis for the relationship between job security, job embeddedness, work engagement and intention to stay at work. It also contributes to the development of the field by contributing to the body of existing information. Moreover, the study offers theoretical and practical consequences for scholars and practitioners in the textile and manufacturing industries.